Analisis Sistem Elektronik Kinerja (E-Kinerja) dalam Meningkatkan Kinerja Pegawai pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Denpasar - Veratiani, Gek Aris; Winaya, I Ketut; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2019)
ABSTRACT Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Denpasar city implements an Electronic performance system (e-kinerja) as a form of e-government development to control the performance of employees through the assessment of Employee Performance Standards (SKP), as well as the basis for granting performance benefits. The regulations governed by the e-performance (e-kinerja) are contained in the Denpasar Mayor Regulation No. 38 of 2017 concerning the Amount of Additional Income Based on Work Achievement in Civil Servants (PNS).Indicate that all performance indicators have been included in the management of e-performance systems and can improve employee performance from the increase in employee performance target values ??(SKP), the increased of community satisfaction, and the increased of retribution income in 2017-2018, but there were still shortcomings, namely the absence of operational standards, the ability of civil servants who cannot use technology and overlapping systems. Keywords : Sistem Elektronik Kinerja (E-Kinerja), Employee Performance, Electronic Government (E-government)